The Influence of Message Source Credibility, Content-Based Trust, and Engagement-Based Trust on Member Contribution Performance through Social Media Engagement with the Moderation of Community Manager in the FRC Ecosystem of PT. MSBU Konsultan Indonesia - Septiasari Septiasari; Denny Bernardus Kurnia Wahyudono; Halek Mu’min (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Professional digital communities face a persistent paradox wherein high member engagement does not reliably translate into substantive contribution performance. Objective: This study developed and tested a moderated mediation model examining the roles of Message Source Credibility, Content-Based Trust, and Engagement-Based Trust as antecedents of Social Media Engagement, which subsequently predicts Member Contribution Performance, moderated by Community Manager Support. Methods: Grounded in Source Credibility Theory, Trust Theory, and Engagement Theory, the study employed a quantitative explanatory design with purposive sampling of 140 active members of the FRC Ecosystem, PT. MSBU Konsultan Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. Results: All nine hypotheses were supported. Engagement-Based Trust emerged as the strongest antecedent of Social Media Engagement, establishing the primacy of relational-affective over informational-cognitive mechanisms in professional community engagement formation. Social Media Engagement demonstrated a dominant effect on Member Contribution Performance, repositioning engagement as a conversion mechanism rather than a terminal outcome. Community Manager Support both directly influenced contribution performance and positively moderated the engagement–contribution relationship, functioning as a governance amplifier. Full mediation across all indirect pathways resolved contradictory findings in prior literature regarding the trust–contribution relationship. Conclusion: These findings advance engagement and community governance theory while providing evidence-based implications for professional digital community governance design. Community practitioners are advised to prioritize relational trust cultivation, implement structured recognition systems, and calibrate managerial support intensity proportionate to observed engagement levels.